Theory of computer science: automata,languages and computation - Mishra, K.L.P (PHI Learning, 2011)
Theory of computer science: automata,languages and computation / Mishra, K.L.P.. -- New Delhi: PHI Learning, 2011 006.3 M678e3 3rd ed. No. of Copies : 1